Implementation of the 2013 Curriculum Based on a Scientific Approach (Case Study at SD Cluster II Kintamani) - Wulandari, I Gusti A A (International Journal of Elementary Education, 2020)
Curriculum changes often occur in the world of education, as we know that the current curriculum used in education units is the 2013 curriculum. With the change in the curriculum, teachers should know the important points in the 2013 curriculum, namely: (1) knowledge of the 2013 curriculum; (2) skills in designing the 2013 curriculum learning tools; (3) the skills to implement the 2013 curriculum. Therefore, this study aims to analyze: the understanding of elementary school homeroom teachers in Cluster II Kintamani regarding the implementation of the 2013 curriculum based on a scientific approach, the skills of homeroom teachers in preparing the 2013 curriculum lesson-based approach scientific, and the skills of homeroom teachers in applying the 2013 curriculum lesson plan based on the scientific approach. This research uses a descriptive qualitative approach. This research was conducted by involving 9 homeroom teachers in Gugus II Kintamani. The data in this study were collected using the interview method, documentation study, and observation. Data were analyzed using data reduction techniques and data verification was carried out on respondents and documentary evidence. The results of this study indicate that the homeroom teachers of Kintamani cluster II understand and are able to design the 2013 curriculum lesson plan based on a scientific approach, but not all teachers are able to implement it properly. According to the results of this study, continuous assistance is needed so that the implementation of the 2013 curriculum based on a scientific approach can be carried out properly by teachers.